THE RELATIONSHIPS OF STUDENTS ADMISSION PROCESS AND ACADEMIC ACHIEVEMENT - Asty Amalia Nurhadi; Shelly Salmah; Muhammad Nasrum Massi; Firdaus Kasim (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: The selection process in medical schools should be able to identify individuals that mostprobably will successfully complete their education. In Faculty of Medicine Hasanuddin University (FMHU)the selection processes are Seleksi Nasional Masuk Perguruan Tinggi Negeri), SBMPTN (Seleksi BersamaMasuk Perguruan Tinggi Negeri), JNS (Jalur Non Subsidi) and International students. Looking at the variousselection methods in FMHU, this study aimed to see how each selection method related with students’academic achievement.Methods: This study compared academic achievement in two semesters at three academic admission students(2014, 2015 and 2016), for four admission processes. The data consist of 308 students from batch of 2014, 308students from batch of 2015, and 320 students from batch of 2016. The analysis was conducted in descriptiveanalysis, One Way ANOVA, and followed by Post-hoc Bonferroni Test.Results: There was significant difference of students GPA for each type of admission. The highest academicachievement was obtained by students from International and SNMPTN admission while the lowest academicachievement was obtained by students from SBMPTN and JNS.Conclusion: Students from International and SNMPTN admission had the highest academic achievementcompared to SBMPTN and JNS. This study showed that there should be an evaluation of the assessment usedin SBMPTN and to continue the use of SNMPTN as one of the main admission route at FMHU.